Government regulations, biosecurity awareness, and farmers' adoption of biosecurity measures: Evidence from pig farmers in Sichuan Province, China - Li, Jianqiang; Yuan, Mengge; Wang, Huan; Zhou, Kun (Frontiers in Sustainable Food Systems, 2023)
To date, African swine fever (ASF) is the greatest challenge to sustainable development in the pig farming industry in Sichuan and elsewhere. Biosecurity measures adopted by farmers are an important way to prevent ASF. As a way to advocate the adoption of biosecurity measures by farmers, government regulations (GRs) can guide and promote farmers' biosecurity awareness and adoption of related measures and thereby support the sustainable development of pig farming. In this study, a theoretical framework for systematic analysis is established, and survey data of 351 pig farmers are used to estimate the effects of GRs on the farmers' adoption of biosecurity measures. The main conclusions are as follows. (1) The different types of GRs all pass the significance test and promote farmers' adoption of biosecurity measures, indicating that the Chinese government's biosecurity policies at this stage are effective. (2) According to a mediation effect model, GRs can promote farmers' adoption of biosecurity measures by increasing the level of biosecurity awareness among farmers. (3) From the results of a heterogeneity test, the effects of GRs on the adoption of biosecurity measures among farmers in the low rearing income level, short rearing time and low rearing scale groups are much greater than those in the high rearing income level, long rearing time and high rearing scale groups. Based on the above conclusions, the results of this study suggest that the government should continue to strengthen GRs, especially guided GRs, such as biosecurity measure training. Moreover, for farmers with different backgrounds, the government should adopt distinct strategies to improve the effectiveness of GRs.